Epidemiology of hypospadias in Europe: a registry-based study - Bergman, Jorieke E. H. (World J Urol, 2015)
BACKGROUND: Hypospadias is a common congenital malformation. The prevalence of hypospadias has a large geographical variation, and recent studies have reported both increasing and decreasing temporal trends. It is unclear whether hypospadias prevalence is associated with maternal age. AIM: To analyze the prevalence and trends of total hypospadias, isolated hypospadias, hypospadias with multiple congenital anomalies, hypospadias with a known cause, and hypospadias severity subtypes in Europe over a 10-year period and to investigate whether maternal age is associated with hypospadias. METHODS: We included all children with hypospadias born from 2001 to 2010 who were registered in 23 EUROCAT registries. Information on the total number of births and maternal age distribution for the registry population was also provided. We analyzed the total prevalence of hypospadias and relative risks by maternal age. RESULTS: From 2001 to 2010, 10,929 hypospadias cases were registered in 5,871,855 births, yielding a total prevalence of 18.61 per 10,000 births. Prevalence varied considerably between different registries, probably due to differences in ascertainment of hypospadias cases. No significant temporal trends were observed with the exceptions of an increasing trend for anterior and posterior hypospadias and a decreasing trend for unspecified hypospadias. After adjusting for registry effects, maternal age was not significantly associated with hypospadias. CONCLUSIONS: Total hypospadias prevalence was stable in 23 EUROCAT registries from 2001 to 2010 and was not significantly influenced by maternal age.